Multiplikatif Jeodeziklerin Geometrisi - Aydın, Muhittin Evren; Dilmen, Esra; Yaman, Gülşah (Fırat University, 2025)
Bu makalede R_*^n multiplikatif Öklid uzayın ve bu uzayda bulunan bazı multiplikatif yüzeylerin jeodezikleri araştırıldı. İlk olarak R_*^n uzayının jeodezikleri elde edildi. R_*^n uzayında multiplikatif silindirler ve multiplikatif koniler üzerindeki multiplikatif jeodezikler sınıflandırıldı. Son olarak multiplikatif helis yüzeyleri tanımlanıp multiplikatif jeodezikleri karakterize edildi.

In this paper, the geodesics of the multiplicative Euclidean space R_*^n and some multiplicative surfaces in this space are investigated. First, the geodesics of the space R_*^n are obtained. The multiplicative geodesics on multiplicative cylinders and multiplicative cones in R_*^n are classified. Finally, multiplicative helix surfaces are defined, and their multiplicative geodesics are characterized.
Geometry of Multiplicative Geodesics
Keywords: Algebraic and Differential Geometry; Cebirsel ve Diferansiyel Geometri